Ethical issues in the evaluation of adults with suspected genetic neuromuscular disorders. Issue 6 (1st October 2016) - Su, Xiaowei; Kang, Peter B.; Russell, James A.; Simmons, Zachary
ABSTRACT: Genetic testing is rapidly becoming an increasingly significant part of the diagnostic armamentarium of neuromuscular clinicians. Although technically easy to order, the results of such testing, whether positive or negative, have potentially enormous consequences for the individual tested and for family members. As a result, ethical considerations must be in the forefront of the physician's agenda when obtaining genetic testing. Informed consent is an important starting point for discussions between physicians and patients, but the counseling embedded in the informed consent process must be an ongoing part of subsequent interactions, including return of results and follow‐up. Patient autonomy, including the right to know and right not‐to‐know results, must be respected. Considerations of capacity, physician beneficence and nonmaleficence, and privacy all play roles in the process. Muscle Nerve 54 : 997–1006, 2016